An exploratory study of the perceptions and experiences of homeless persons regarding service provision by Khulisa Solutions, a non-governmental organisation in the Western Cape - Nzula, Nontsikelelo (Department of Social Development, 2018)
This study explored the perceptions and experiences of homeless people regarding welfare service provision by Khulisa Solutions, an NGO that provides services to homeless people in the Western Cape. To this end, using primarily a social development perspective, the study focused on five objectives: assessing the available services for homeless people related to shelter, food, employment and health services in general; exploring the perceptions and experiences of homeless persons in accessing welfare services at Khulisa; identifying the strengths and weaknesses of available services for the homeless as provided by Khulisa; examining if homeless people were aware of the services available to them, and assessing the overall challenges in service provision for the homeless. An exploratory qualitative methodology was used through the administration of 15 in depth face to face interviews using a semi-structured interview schedule. Purposive non-probability sampling selection was implemented focusing on homeless beneficiaries of Khulisa services and the Carpenters Shop an affiliate service provider to Khulisa. The findings of the study revealed that food services were the most accessible and reliable services to the homeless providing both stability and routine. Shelter services provided a physical and psychological haven as well as opportunities for employment and self-development. The access to shelter benefits was however, limited as the majority of participants found shelter services too expensive or that the shelters were structured to perpetuate the exclusion of homeless families. Participants showed extensive knowledge about where to access health care services which however did not translate into the frequent use of such services. Employment services were criticised for only providing temporary employment and not providing opportunities for skills development. Khulisa Solutions was highly commended for providing long term employment as well as involving beneficiaries in the growth of projects. Beneficiaries indicated a need for a similar emphasis and input on shelter service provision by Khulisa which was not their main focus of service delivery. Recommendations are made based on the findings of the study which are inclusive of solutions proposed by the participants.